# Calculator search results

Formula
Solve the quadratic equation
Answer
Number of solution
Answer
Relationship between roots and coefficients
Answer
Graph
$y = x ^ { 2 } - 3 x$
$y = 18$
$x$-intercept
$\left ( 3 , 0 \right )$, $\left ( 0 , 0 \right )$
$y$-intercept
$\left ( 0 , 0 \right )$
Minimum
$\left ( \dfrac { 3 } { 2 } , - \dfrac { 9 } { 4 } \right )$
Standard form
$y = \left ( x - \dfrac { 3 } { 2 } \right ) ^ { 2 } - \dfrac { 9 } { 4 }$
$x ^{ 2 } -3x = 18$
$\begin{array} {l} x = 6 \\ x = - 3 \end{array}$
Find solution by method of factorization
$x ^ { 2 } - 3 x = \color{#FF6800}{ 18 }$
 Move the expression to the left side and change the symbol 
$x ^ { 2 } - 3 x \color{#FF6800}{ - } \color{#FF6800}{ 18 } = 0$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } = 0$
$acx^{2} + \left(ad + bc\right)x +bd = \left(ax + b\right)\left(cx+d\right)$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = 0$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 } \right ) \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) = \color{#FF6800}{ 0 }$
 If the product of the factor is 0, at least one factor should be 0 
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 } = \color{#FF6800}{ 0 } \\ \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \color{#FF6800}{ 0 } \end{array}$
 Solve the equation to find $x$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 6 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{array}$
$\begin{array} {l} x = 6 \\ x = - 3 \end{array}$
Solve quadratic equations using the square root
$x ^ { 2 } - 3 x = \color{#FF6800}{ 18 }$
 Move the expression to the left side and change the symbol 
$x ^ { 2 } - 3 x \color{#FF6800}{ - } \color{#FF6800}{ 18 } = 0$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 18 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - \dfrac { 3 } { 2 } \right ) ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 18 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
 Move the constant to the right side and change the sign 
$\left ( x - \dfrac { 3 } { 2 } \right ) ^ { 2 } = \color{#FF6800}{ 18 } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x - \dfrac { 3 } { 2 } \right ) ^ { 2 } = 18 + \left ( \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
 When raising a fraction to the power, raise the numerator and denominator each to the power 
$\left ( x - \dfrac { 3 } { 2 } \right ) ^ { 2 } = 18 + \dfrac { \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 18 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 ^ { 2 } } { 2 ^ { 2 } } }$
 Organize the expression 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 81 } { 4 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 81 } { 4 } }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 81 } { 4 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 3 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 81 } { 4 } } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 9 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 2 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { 9 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 3 } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 9 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 9 } { 2 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 9 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 9 } { 2 } } \end{array}$
 Organize the expression 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 6 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{array}$
$\begin{array} {l} x = 6 \\ x = - 3 \end{array}$
Calculate using the quadratic formula
$x ^ { 2 } - 3 x = \color{#FF6800}{ 18 }$
 Move the expression to the left side and change the symbol 
$x ^ { 2 } - 3 x \color{#FF6800}{ - } \color{#FF6800}{ 18 } = 0$
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 3 \right ) \pm \sqrt{ \left ( - 3 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 18 \right ) } } { 2 \times 1 }$
 Simplify Minus 
$x = \dfrac { 3 \pm \sqrt{ \left ( - 3 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 18 \right ) } } { 2 \times 1 }$
$x = \dfrac { 3 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 18 \right ) } } { 2 \times 1 }$
 Remove negative signs because negative numbers raised to even powers are positive 
$x = \dfrac { 3 \pm \sqrt{ 3 ^ { 2 } - 4 \times 1 \times \left ( - 18 \right ) } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 \pm \sqrt{ 3 ^ { 2 } - 4 \times 1 \times \left ( - 18 \right ) } } { 2 \times 1 } }$
 Organize the expression 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 \pm \sqrt{ 81 } } { 2 \times 1 } }$
$x = \dfrac { 3 \pm \sqrt{ \color{#FF6800}{ 81 } } } { 2 \times 1 }$
 Organize the part that can be taken out of the radical sign inside the square root symbol 
$x = \dfrac { 3 \pm \color{#FF6800}{ 9 } } { 2 \times 1 }$
$x = \dfrac { 3 \pm 9 } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
 Multiplying any number by 1 does not change the value 
$x = \dfrac { 3 \pm 9 } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 \pm 9 } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 + 9 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 3 - 9 } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 9 } } { 2 } \\ x = \dfrac { 3 - 9 } { 2 } \end{array}$
 Add $3$ and $9$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 12 } } { 2 } \\ x = \dfrac { 3 - 9 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 12 } { 2 } } \\ x = \dfrac { 3 - 9 } { 2 } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 6 } { 1 } } \\ x = \dfrac { 3 - 9 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 6 } { 1 } } \\ x = \dfrac { 3 - 9 } { 2 } \end{array}$
 Reduce the fraction to the lowest term 
$\begin{array} {l} x = \color{#FF6800}{ 6 } \\ x = \dfrac { 3 - 9 } { 2 } \end{array}$
$\begin{array} {l} x = 6 \\ x = \dfrac { \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 9 } } { 2 } \end{array}$
 Subtract $9$ from $3$
$\begin{array} {l} x = 6 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 6 } } { 2 } \end{array}$
$\begin{array} {l} x = 6 \\ x = \color{#FF6800}{ \dfrac { - 6 } { 2 } } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = 6 \\ x = \color{#FF6800}{ \dfrac { - 3 } { 1 } } \end{array}$
$\begin{array} {l} x = 6 \\ x = \dfrac { - 3 } { \color{#FF6800}{ 1 } } \end{array}$
 If the denominator is 1, the denominator can be removed 
$\begin{array} {l} x = 6 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \end{array}$
 2 real roots 
Find the number of solutions
$x ^ { 2 } - 3 x = \color{#FF6800}{ 18 }$
 Move the expression to the left side and change the symbol 
$x ^ { 2 } - 3 x \color{#FF6800}{ - } \color{#FF6800}{ 18 } = 0$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } = \color{#FF6800}{ 0 }$
 Determine the number of roots using discriminant, $D=b^{2}-4ac$ from quadratic equation, $ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 18 } \right )$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 18 \right )$
 Remove negative signs because negative numbers raised to even powers are positive 
$D = 3 ^ { 2 } - 4 \times 1 \times \left ( - 18 \right )$
$D = \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 18 \right )$
 Calculate power 
$D = \color{#FF6800}{ 9 } - 4 \times 1 \times \left ( - 18 \right )$
$D = 9 - 4 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \times \left ( - 18 \right )$
 Multiplying any number by 1 does not change the value 
$D = 9 - 4 \times \left ( - 18 \right )$
$D = 9 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 18 } \right )$
 Multiply $- 4$ and $- 18$
$D = 9 + \color{#FF6800}{ 72 }$
$D = \color{#FF6800}{ 9 } \color{#FF6800}{ + } \color{#FF6800}{ 72 }$
 Add $9$ and $72$
$D = \color{#FF6800}{ 81 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 81 }$
 Since $D>0$ , the number of real root of the following quadratic equation is 2 
 2 real roots 
$\alpha + \beta = 3 , \alpha \beta = - 18$
Find the sum and product of the two roots of the quadratic equation
$x ^ { 2 } - 3 x = \color{#FF6800}{ 18 }$
 Move the expression to the left side and change the symbol 
$x ^ { 2 } - 3 x \color{#FF6800}{ - } \color{#FF6800}{ 18 } = 0$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } = \color{#FF6800}{ 0 }$
 In the quadratic equation $ax^{2}+bx+c=0$ , if the two roots are $\alpha, \beta$ , then it is $\alpha + \beta =-\dfrac{b}{a}$ , $\alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 3 } { 1 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { - 18 } { 1 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 3 } { 1 } } , \alpha \beta = \dfrac { - 18 } { 1 }$
 Solve the sign of a fraction with a negative sign 
$\alpha + \beta = \color{#FF6800}{ \dfrac { 3 } { 1 } } , \alpha \beta = \dfrac { - 18 } { 1 }$
$\alpha + \beta = \dfrac { 3 } { \color{#FF6800}{ 1 } } , \alpha \beta = \dfrac { - 18 } { 1 }$
 If the denominator is 1, the denominator can be removed 
$\alpha + \beta = \color{#FF6800}{ 3 } , \alpha \beta = \dfrac { - 18 } { 1 }$
$\alpha + \beta = 3 , \alpha \beta = \dfrac { - 18 } { \color{#FF6800}{ 1 } }$
 If the denominator is 1, the denominator can be removed 
$\alpha + \beta = 3 , \alpha \beta = \color{#FF6800}{ - } \color{#FF6800}{ 18 }$
 그래프 보기 
Graph
Solution search results
7th-9th grade
Other
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture